Catastrophic injuries in the Olympic styles of wrestling in Iran - Kordi, R.; Akbarnejad, A.; Wallace, W. A. (British Journal of Sports Medicine, 2010)
Objectives: In this study, a profile of direct catastrophic injuries in international styles of wrestling was developed, and the possible risk factors were described.